PENGUKURAN TEKANAN UDARA MENGGUNAKAN DT-SENSE BAROMETRIC PRESURE BERBASIS SENSOR HP03 - Yulkifli, Yulkifli; Asrizal, Asrizal; Ardi, Ruci (IAIN Batusangkar, 2014)
This research has successfully designed an instrument to measure air pressure, namely, DT-Sense Barometric Pressure and Temperature (DT-SBPT). DT-SBPT is a smart sensor module on the basis of HP03 sensor. Data were collected using direct and indirect measurement. Direct measurement was done toward air pressure. Indirect measurement, however, was applied to determine the exact and accuracy of the measurement of air pressure. Data were analyzed by using two ways, namely statistic and graphic ways. The result of the research shows that DT-SBPT has high appropriateness and accuracy, which is 0.99. The air pressure around earth surface decrease linearly when the height increase.Keywords: air pressure, smart sensor module